Women's experiences of pregnancy related pelvic girdle pain: A systematic review. (January 2018) - Mackenzie, Jo; Murray, Esther; Lusher, Joanne
Abstract: Objective: to systematically review the available studies which relay the experience of pregnancy related pelvic girdle pain and how this affects women psychologically and emotionally. Method: a systematic review and meta-synthesis of the experiences of pregnancy related pelvic girdle pain was conducted for qualitative studies dated between 2005 and 2016. Predefined terms were used to search nine central databases and hand searches of two reference lists of identified studies were carried out. Findings: 614 records were identified, eight studies met the inclusion criteria for review. Pain from pelvic girdle pain impacted on women's daily lives both at home and the workplace. This had a negative emotional and psychological impact on women as it took away their feeling of independence. Women reported feelings of frustration, guilt, irritability and upset at being unable to carry out their normal roles. Pelvic girdle pain also affected the women's sense of identity and ability to care for their children. Conclusions and implications for practice: Health professionals working with pregnant and postnatal women need to be aware of the anger, frustration and negative emotions resulting from PGP. These women may become socially isolated and there is a risk they could abuse analgesics in attempt to manage the pain especially if they do not have the social support. For women with young children, it is important to be aware of safety issues they face with carrying babies and controlling toddlers. It is therefore important that health professionals recognise PGP as a serious health issue, approach this condition sensitively and refer to appropriate treatment as soon as PGP is suspected. Highlights: Pregnancy related pelvic girdle pain negatively impacts daily life for women. Pain from pelvic girdle pain disrupts the mother-child(ren) relationship. Women suffer from negative emotional and psychological effects due to pain. The women are unprepared for the pain which dominates their lives. Pelvic girdle pain affects all the family.